BETRAYAL THAT DISMANTLES THE NATION, OBSTRUCTED JUSTICE, AND A POWERLESS CITIZENRY: SEEKING LEGITIMATE REMEDIES BEYOND THE LIMITS OF DOMESTIC AND INTERNATIONAL LAW - Dr. Siddik Arslan (American Journals Publishing, 2025)
This study addresses the question of what normative and ethical foundations societies can rely upon to develop legitimate solutions in extreme crisis scenarios where the law has become entirely dysfunctional and state capacity has collapsed. The research demonstrates that treason is not merely an individual criminal offense but rather a systemic rupture process that simultaneously targets state capacity, institutional integrity, social trust, and collective memory. Positioned at the intersection of political science, sociology of law, ethical theories, transitional justice, and social psychology literatures, this study adopts an interdisciplinary perspective. The research employs conceptual analysis, historical comparison, and theoretical synthesis approaches within a qualitative methodological framework. The most fundamental theoretical contribution of this study is the development of an "integrated legitimacy model" that becomes essential under conditions of treason and legal paralysis. This model does not reduce legitimacy merely to existing legal norms; rather, it defines legitimacy as a dynamic structure built upon four fundamental pillars: legal validity, ethical justifiability, social consensus, and institutional resilience. The findings demonstrate that during periods of complete legal collapse, societies can develop alternative sources of legitimacy by turning to ethical norms, deliberative processes, restorative justice mechanisms, and collective solidarity networks. The study has established that ethical leadership constitutes a decisive variable in the reconstruction of legitimacy, that the collapse of the information order perpetuates legitimacy crises, and that societal resilience directly affects recovery processes. By emphasizing the limitations of international law, the study reveals the importance of local legitimacy sources. Policy recommendations encompass the integrated treatment of legal reforms, institutionalization of ethical leadership, information ecosystem security, economic stability, and social solidarity. This study argues that legitimacy cannot be reduced solely to written laws, and systematically develops the concept of "legitimacy beyond law" by asserting that social conscience, collective memory, and ethical norms constitute indispensable sources of legitimacy.
Keywords: Treason, legitimacy crisis, legal paralysis, integrated legitimacy model, transitional justice, societal resilience, ethical leadership